The Brand Authenticity Continuum: Strategic Approaches for Building Value - Napoli, Julie; Dickinson, Sonia; Beverland, M. (American Marketing Association, 2016)
This article empirically examines the value derived by consumers through their use and consumption of authentic brands and the indirect value attributable to a brand. Our findings provide an understanding of the drivers of value along an authenticity continuum. We demonstrate that authenticity cues of quality commitment, heritage and sincerity have differential effects on a brand’s position along the authenticity continuum and consequently, authenticity strategies. This paper discusses implications where initially, brands move along the continuum with internally driven strategies (germination, cultivation and consolidation). However, to attain very high levels of authenticity, brands pursue an externally driven strategy (preservation) that acknowledges external stakeholder roles in the creation of very highly authentic brands. Directions for future research are also discussed.